Sustainability of a community‐based anti‐retroviral care delivery model – a qualitative research study in Tete, Mozambique. Issue 2 (6th October 2014) - Rasschaert, Freya; Decroo, Tom; Remartinez, Daniel; Telfer, Barbara; Lessitala, Faustino; Biot, Marc; Candrinho, Baltazar; Van Damme, Wim
Abstract : Introduction: To overcome patients' reported barriers to accessing anti‐retroviral therapy (ART), a community‐based delivery model was piloted in Tete, Mozambique. Community ART Groups (CAGs) of maximum six patients stable on ART offered cost‐ and time‐saving benefits and mutual psychosocial support, which resulted in better adherence and retention outcomes. To date, Médecins Sans Frontières has coordinated and supported these community‐driven activities. Methods: To better understand the sustainability of the CAG model, we developed a conceptual framework on sustainability of community‐based programmes. This was used to explore the data retrieved from 16 focus group discussions and 24 in‐depth interviews with different stakeholder groups involved in the CAG model and to identify factors influencing the sustainability of the CAG model. Results: We report the findings according to the framework's five components. (1) The CAG model was designed to overcome patients' barriers to ART and was built on a concept of self‐management and patient empowerment to reach effective results. (2) Despite the progressive Ministry of Health (MoH) involvement, the daily management of the model is still strongly dependent on external resources, especially the need for a regulatory cadre to form and monitor the groups. These additional resources are in contrast to the limited MoH resources available. (3) The model is strongly embedded in the community, with patients taking a more active role in their own healthcare and that of their peers. They are considered as partners in healthcare, which implies a new healthcare approach. (4) There is a growing enabling environment with political will and general acceptance to support the CAG model. (5) However, contextual factors, such as poverty, illiteracy and the weak health system, influence the community‐based model and need to be addressed. Conclusions: The community embeddedness of the model, together with patient empowerment, high acceptability and progressive MoH involvement strongly favour the future sustainability of the CAG model. The high dependency on external resources for the model's daily management, however, can potentially jeopardize its sustainability. Further reflections are required on possible solutions to solve these challenges, especially in terms of human resources.